Poverty alleviation in Mogadishu, Somalia: the role of Islamic microfinance - Xalani, Mohamed Abdi Elmi; Che Mohd Salleh, Marhanum (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
The objective of this paper is to empirically examine the role of Islamic microfinance in poverty alleviation in Mogadishu, Somalia. The study basically concerns on two objectives which are; to observe the current practice of Islamic microfinance in Mogadishu, Somalia, and to investigate the effectiveness of Islamic microfinance institutions in this country towards poverty reduction. To achieve the research objectives, quantitative methodology is adopted and primary data is relied on for analysis. Based on survey questionnaire, the sample of this research were microfinance recipients in Mogadishu, Somalia. Via descriptive analysis, it is revealed that the current practice of Islamic microfinance activities in Mogadishu, Somalia is serving the poor people, but these microfinance activities are not effective in terms of the procedure of obtaining loans, enhancement of standard living, usefulness of the system, and the awareness level of the people. In addition, the findings of this study will be beneficial for the Islamic microfinance institutions, Islamic banks who involve microfinance services, enterprises, academicians and researchers who interest in this area.